Nuclear Receptors Regulate Intestinal Inflammation in the Context of IBD - Klepsch, Victoria; Moschen, Alexander R.; Tilg, Herbert; Baier, Gottfried; Hermann-Kleiter, Natascha (Frontiers in Immunology, 2019)
Gastrointestinal (GI) homeostasis is strongly dependent on nuclear receptor (NR) functions. They play a variety of roles ranging from nutrient uptake, sensing of microbial metabolites, regulation of epithelial intestinal cell integrity to the shaping of the intestinal immune cell repertoire. Several NRs are associated with GI pathologies; therefore, systematic analysis of NR biology, the underlying molecular mechanisms, and regulation of target genes can be expected to help greatly in uncovering the course of GI diseases. Recently, an increasing number of NRs has been validated as a potential drug target for therapeutic intervention in patients with inflammatory bowel disease (IBD). Besides the classical glucocorticoids, especially PPARgamma, VDR, or PXR-selective ligands are currently being tested with promising results in clinical IBD trials. Also, several pre-clinical animal studies are performed with NRs. This review focuses on the complex NR network and its biology in the gastrointestinal tract with special attention paid to NRs that have already been pharmacologically targeted in the clinic and pre-clinical IBD treatment regimens.